2006
DOI: 10.1016/j.ejpain.2005.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Decreased muscle blood flow in fibromyalgia patients during standardised muscle exercise: A contrast media enhanced colour doppler study

Abstract: The aim of the study was to investigate if contrast enhanced ultrasound (US) imaging of muscular blood flow during and following exercise could detect alterations in vascularity in fibromyalgia (FM) patients. Ten FM patients and 10 matched controls were examined with US during standardised static and directly following static and dynamic muscular contractions of the infraspinatus muscle. Doppler ultrasound evaluation was performed before and after the administration of ultrasound contrast media. The FM patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(94 citation statements)
references
References 47 publications
3
84
1
5
Order By: Relevance
“…Bertmaring et al suggested that results obtained with IR thermography were sensitive to fatigue of the musculoskeletal system; however, various factors such as blood flow or muscle heating could affect the skin surface temperature [35]. The results of other studies also indicate that muscle effort causes changes in blood flow [27,28,29]. The changes in temperature on the surface of the skin, observed in the present study, may result not only from muscle heating but also from other factors such as blood flow.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Bertmaring et al suggested that results obtained with IR thermography were sensitive to fatigue of the musculoskeletal system; however, various factors such as blood flow or muscle heating could affect the skin surface temperature [35]. The results of other studies also indicate that muscle effort causes changes in blood flow [27,28,29]. The changes in temperature on the surface of the skin, observed in the present study, may result not only from muscle heating but also from other factors such as blood flow.…”
Section: Discussionsupporting
confidence: 64%
“…Invasive experiments, with biochemical indicators (CrP, ATP, ADP) show changes in time of load even at levels under 10% MVC [25]. The results indicate that low-level effort causes changes in blood pressure, heart rate and blood flow [27,28,29]. Moreover, studies with the use of surface EMG show fatigue at levels of muscle contraction as low as 8% MVC [26].…”
Section: Introductionmentioning
confidence: 88%
“…Characterization of circulatory and metabolic function in skeletal muscle has important applications in exercise and sports medicine [1][2][3][4][5] and provides key information for understanding many common diseases (e.g., peripheral vascular disease, [6][7][8] fibromyalgia, 9 heart failure 10,11 ) affecting skeletal muscle. Because differences between healthy and diseased populations are not always apparent at rest, it is important to study muscle hemodynamic and metabolic changes in response to stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired blood flow to the pain region has been observed in persons with both chronic regional and widespread pain during various provocations, e.g., cold water, needle stimulation by acupuncture, and static or dynamic contractions (Acero et al 1999;Larsson et al 1999;Sandberg et al 2005;Elvin et al 2006;; for comprehensive reviews on this topic see Passatore and Roatta (2006) and Vierck (2006).…”
Section: Insufficient Blood Flow Regulation In Chronic Muscle Painmentioning
confidence: 99%